Lactobacillus gasseri JM1 pre-acidification induced regulation in the flavor profile of beer processes - Shasha Cheng; Yu Zhang; Heng Zhou; Zhen Huang; Haifu Jia; Yujun Jiang; Hao Wang; Chaoxin Man (Food Chemistry: X)
Acidification influences the flavor profile of beer. Lactobacillus gasseri JM1 was utilized to acidify wort, examining its impact on key beer preparation processes and exploring the mechanisms behind flavor alterations. The results demonstrated that acidification by L. gasseri JM1 increased lactic acid and hexanoic acid levels in the wort, and elevated the concentrations of aldehydes (hexanal), esters (hexanoic acid, ethyl ester), and lactones (2(3H)-furanone, dihydro-5-pentyl- and 2(3H)-furanone, 5-hexyldihydro-) in both boiled and fermented products. Additionally, acidification enriched the flavor profile of post-boil samples, enhancing flavors of citrus, fatty, floral, fresh, fruity, green, sweet, and waxy. And the key aroma-active compounds in the acidified beer were identified as 1-octen-3-ol (decreased); and hexanoic acid, ethyl ester; 2(3H)-furanone, dihydro-5-pentyl-; and 2(3H)-furanone, 5-hexyldihydro- (increased). These changes led to a reduction of green flavor and an enhancement of waxy flavor. This provides a theoretical basis for regulating the application of L. gasseri JM1 to beer.